Structure of the pseudokinase VRK3 reveals a degraded catalytic site, a highly conserved kinase fold, and a putative regulatory binding site. - Scheeff, E; Eswaran, J; Bunkoczi, G; Knapp, S; Manning, G (Cell Press, 2009)
About 10% of all protein kinases are predicted to be enzymatically inactive pseudokinases, but the structural details of kinase inactivation have remained unclear. We present the first structure of a pseudokinase, VRK3, and that of its closest active relative, VRK2. Profound changes to the active site region underlie the loss of catalytic activity, and VRK3 cannot bind ATP because of residue substitutions in the binding pocket. However, VRK3 still shares striking structural similarity with VRK2, and appears to be locked in a pseudoactive conformation. VRK3 also conserves residue interactions that are surprising in the absence of enzymatic function; these appear to play important architectural roles required for the residual functions of VRK3. Remarkably, VRK3 has an "inverted" pattern of sequence conservation: although the active site is poorly conserved, portions of the molecular surface show very high conservation, suggesting that they form key interactions that explain the evolutionary retention of VRK3.